The Correlation between Students’ Achievement in Using Adjectives and Their Ability in Writing Descriptive Text - Chadafi, Mo'amar; Rasuan, Zulfikri Betyar; Novrieta, Dina (EEdJ: English Education Journal, 2023)
This study was a correlational study. The objectives of this study were: to find out the students’ achievement in using adjective, their ability in writing descriptive text, and whether there was any significant correlation between those two variables. The total number of sample was 24 students. The findings of this study showed that the students’ achievement in using adjective was categorized into good criteria. It could be seen from the result of the mean score of students’ achievement in using adjective, it was 76.96. For the students’ ability in writing descriptive text, the findings of the study showed that the result of the mean score was 76.75. Then, the findings for the correlation between students’ achievement in using adjective and students’ ability in writing descriptive text was 0.860 and the p-value (Sig. (2- tailed)) was 0.000. Meanwhile, the critical value in the table at significant (2- tailed) level 5% was 0.404. It meant that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Therefore, there was a positive correlation between students’ achievement in using adjective and students’ ability in writing descriptive text.